A Certain Age Colonial Jakarta through the Memories of Its Intellectuals - Mrázek, Rudolf (Duke University Press, 2010)
'A Certain Age' is an unconventional, evocative work of history and a moving reflection on memory, modernity, space, time, and the limitations of traditional historical narratives. Rudolf Mrázek visited Indonesia throughout the 1990s, recording lengthy interviews with elderly intellectuals in and around Jakarta. With few exceptions, they were part of an urban elite born under colonial rule and educated at Dutch schools. From the early twentieth century, through the late colonial era, the national revolution, and well into independence after 1945, these intellectuals injected their ideas of modernity, progress, and freedom into local and national discussion.When Mrázek began his interviews, he expected to discuss phenomena such as the transition from colonialism to postcolonialism. His interviewees, however, wanted to share more personal recollections. Mrázek illuminates their stories of the past with evocative depictions of their late-twentieth-century surroundings.